The influence of teachers' ICT competence on children's digital literacy abilities - Lestari, Gunarti Dwi; Adhe, Kartika Rinakit; Yulianingsih, Wiwin; Rosyanafi, Rofik Jalal; Widyaswari, Monica (Edelweiss Applied Science and Technology, 2025)
The use of digital devices in the learning process is intended to provide convenience for teachers in presenting quality learning for children. Therefore, digital literacy is very much needed by teachers and prospective teachers in order to optimize children's development. This study uses a quantitative research design. The population in this study amounted to 9 respondents from various areas of Surabaya, while the sample in this study was obtained by 45 respondents with the research subjects being kindergarten teachers in the Surabaya area. The sampling technique used was purposive sampling. The data analysis technique used cluster sampling technique. The overall research results show that teacher ICT competence has an effect on children's digital literacy skills, which shows that the variable X teacher ICT competence has a t count of 2.654, which means it is greater than the t table which is 2.01669, and a significant value of 0.011 is smaller than 0.05. So it can be concluded that H1 is accepted so that variable X has a significant effect on variable Y, namely children's digital literacy skills. These results are also supported by the conformity of the results on each question item covering teacher competence in using digital devices in their learning. With the presence of digital devices as a learning resource, it produces children's ability to learn independently and teach children to utilize digital devices to improve knowledge and skills according to their age.